Sistema de informação para unidades prisionais do estado do Rio Grande do Norte- Infosisp - Penha, Andrezza Kharla da Cunha (Universidade Federal Rural do Semi-Árido, 2017)
The Penitentiary System of the Rio Grande do Norte State does not have an information system to control and to manage prisoners and visitors in its prison units, that is, all control records are made on paper and stored in folders and cabinets or on computers without data integration, which may compromise the security, confidentiality, privacy, and integrity of this information. From this issue, the proposal of this paper is to promote a better management of this information by developing an web information system using software engineering techniques. Thus, it will be presented in this work the process of development of a system that will aid in the data control of the Penitentiary System of the Rio Grande do Norte and will also be presented, using an acceptance model, the results generated from tests to validate this system.
Monografia
Keywords: Sistema penitenciário; Modelo de aceitação; INFOSISP; Penitentiary System; Acceptance Model; INFOSISP; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO